THE INFLUENCE OF JOB INSECURITY AND JOB STRESS TOWARDS EMPLOYEE PERFORMANCE AT PT. BANK SULUTGO SUB BRANCH SAM RATULANGI - Peter Anderson Runtu; Frederik G. Worang; Shinta J. C. Wangke (Universitas Sam Ratulangi, 2023)
The purpose of this study is to determine whether job insecurity and job stress affect the performance of employees at PT. Bank SulutGo Sub Branch Sam Ratulangi.The population in this study were all active employees at PT. Bank SulutGo Sub Branch Sam Ratulangi, with a total of 31 employees. The sampling method used in this study is saturated sampling, with a sample of the entire population. The data analysis method used was multiple linear regression analysis using SPSS as a data processing tool.The results of data analysis show that job insecurity has a negative and significant effect on employee performance, and job stress has a positive and significant effect on employee performance. For leaders at this company is expected to be able to issue good policies for the employees and also with the Covid-19 and digitalization era, leaders need to make plans for existing employees so they feel safe and comfortable with their existing jobs. And also the leader must be able to make employees able to maximize the performance of their employees without having to feel stressed. Keywords: job insecurity, job stress, employee performance